2016
DOI: 10.1038/srep20323
|View full text |Cite
|
Sign up to set email alerts
|

Massive and massless Dirac fermions in Pb1−xSnxTe topological crystalline insulator probed by magneto-optical absorption

Abstract: Dirac fermions in condensed matter physics hold great promise for novel fundamental physics, quantum devices and data storage applications. IV-VI semiconductors, in the inverted regime, have been recently shown to exhibit massless topological surface Dirac fermions protected by crystalline symmetry, as well as massive bulk Dirac fermions. Under a strong magnetic field (B), both surface and bulk states are quantized into Landau levels that disperse as B1/2, and are thus difficult to distinguish. In this work, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 44 publications
(88 reference statements)
6
47
2
1
Order By: Relevance
“…The fourfold bulk valley degeneracy combined with the mirror symmetric character of the rock-salt crystal structure of Pb 1-x Sn x Se and Pb 1-x Sn x Te yields a TCI state that hosts fourfold degenerate TSS. 5,15,24,[44][45][46][47][48][49] Despite this subtlety, the band structure and Landau levels of IV-VI semiconductors is ideal to study under the proposed scope, due to their relative simplicity 23,50 compared to other materials such as II-VI and V-VI systems that have highly asymmetric conduction and valence bands. It can actually be shown that a description similar to that of BHZ can be applied to describe the band structure of Pb 1-x Sn x Se and Pb 1-x Sn x Te.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fourfold bulk valley degeneracy combined with the mirror symmetric character of the rock-salt crystal structure of Pb 1-x Sn x Se and Pb 1-x Sn x Te yields a TCI state that hosts fourfold degenerate TSS. 5,15,24,[44][45][46][47][48][49] Despite this subtlety, the band structure and Landau levels of IV-VI semiconductors is ideal to study under the proposed scope, due to their relative simplicity 23,50 compared to other materials such as II-VI and V-VI systems that have highly asymmetric conduction and valence bands. It can actually be shown that a description similar to that of BHZ can be applied to describe the band structure of Pb 1-x Sn x Se and Pb 1-x Sn x Te.…”
Section: Resultsmentioning
confidence: 99%
“…This anisotropy in v D is small for Pb 1-x Sn x Se but rather large for Pb 1-x Sn x Te (Supplement (S3)). 23 The interband transitions in Figs. 3a, b can be well described using a massive Dirac-like Landau-level spectrum given in Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that the LL in IV-IV TCIs can be well described by a massive Dirac spectrum that includes spin-splitting [24] [29] [30] [31], resulting from a 6-band k.p Hamiltonian. [30] If the contributions from the far-bands are neglected a 2-band k.p Hamiltonian results, the solution of which is an ideal massive Dirac model [32].…”
Section: Fig 2 (Color Online) (A)mentioning
confidence: 99%